Identification of antimicrobial peptides from Enterococcus faecium IP5-2a isolated from tilapia gut using mass spectrometry - Feria Zevallos, Manuel (2024)
Antimicrobial peptides are small molecules that exhibit strong antagonistic activity against pathogenic microorganisms and are synthesized by a wide variety or organisms, including probiotic bacteria. The aim of the study was to identify peptides with antimicrobial activity in the Enterococcus faecium IP5-2a strain previously isolated from the intestinal tract of Nile tilapia (Oreochromis niloticus). Cellular and extracelullar proteins extraction was performed, followed by 1D SDS-PAGE gel electrophoresis and MALDI-TOF/TOF mass spectrometry. The results revealed peptides with antimicrobial activity, including P54 (SagA) protein, a bacteriocin-like protein and a lantibiotic. These proteins play an important role in the antagonistic capacity of the E. faecium IP52a strain, allowing it to be considered as a potential probiotic in the aquaculture industry.